Infectious diseases linked to cross-contamination of flexible endoscopes - Kenters, Nikki; Huijskens, Elisabeth G. W.; Meier, Corianne; Voss, Andreas (Endoscopy International Open, 2015)
Flexible endoscopes are widely used to examine, diagnose, and treat medical disorders. While the risk of endoscopy-related transmission of infection is estimated to be very low, more health care-associated infections are related to contaminated endoscopes than to any other medical device. Flexible endoscopes can get highly contaminated with microorganisms, secretions and blood during use. The narrow lumens and multiple internal channels make the cleaning of flexible endoscopes a complex and difficult task.Despite the availability of international, national and local endoscope reprocessing guidelines, contamination and transmission of microorganisms continue to occur. These transmissions are mostly related to the use of defective equipment, endoscope reprocessing failures, and noncompliance with recommended guidelines. This article presents an overview of publications about case reports and outbreaks related to contamination of flexible endoscopes.